Repression of the Transcription Factor Bach2 Contributes to Predisposition of IgG1 Memory B Cells toward Plasma Cell Differentiation - Kometani, Kohei; Nakagawa, Rinako; Shinnakasu, Ryo; Kaji, Tomohiro; Rybouchkin, Andrei; Moriyama, Saya; Furukawa, Koji; Koseki, Haruhiko; Takemori, Toshitada; Kurosaki, Tomohiro (Immunity (Cambridge, Mass.), 2013)
Memory B cells are essential for generating rapid and robust secondary antibody responses. It has been thought that the unique cytoplasmic domain of IgG causes the prompt activation of antigen-experienced IgG memory B cells. To assess this model, we have generated a mouse containing IgG1 B cells that have never encountered antigen. We found that, upon challenge, antigen-experienced IgG1 memory B cells rapidly differentiated into plasma cells, whereas nonexperienced IgG1 B cells did not, suggesting the importance of the stimulation history. In addition, our results suggest that repression of the Bach2 transcription factor, which results from antigen experience, contributes to predisposition of IgG1 memory B cells to differentiate into plasma cells. •IgG1 tail alone cannot explain robust antibody production•Expression of Bach2 is decreased in IgG1 memory B cells•Repression of Bach2 contributes to robust antibody production•mTOR signaling is involved in Bach2 repression